2019
DOI: 10.1155/2019/8573451
|View full text |Cite
|
Sign up to set email alerts
|

Aminopropyl Functionalised MCM-41: Synthesis and Application for Adsorption of Pb(II) and Cd(II)

Abstract: This paper shows a comparison of porous properties of aminopropyl-MCM-41 materials functionalised via the direct and indirect methods. The obtained materials were characterised using X-ray powder diffraction (XRD), transmission electron microscopy (TEM), thermogravimetric analysis-differential scanning calorimeter (TGA-DSC), adsorption/desorption isotherms of nitrogen, and Fourier-transfer infrared (FT-IR) spectroscopy. The results showed that the direct method provided the aminopropyl-MCM-41 material with wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 45 publications
(80 reference statements)
0
20
0
Order By: Relevance
“…Upon ligand (MPTMS and APTMS) grafting on AM41E-120-48, as shown in Figure 4 d, three hk0 diffraction peaks were still visible but decreased in intensities, illustrating the successful ligand grafting and still intact mesoporous structure [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Upon ligand (MPTMS and APTMS) grafting on AM41E-120-48, as shown in Figure 4 d, three hk0 diffraction peaks were still visible but decreased in intensities, illustrating the successful ligand grafting and still intact mesoporous structure [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“… 9 In past years, various investigations have been carried out on the adsorption of heavy metals by mesoporous silica. 10 , 11 These studies resulted in the development of a novel application for MS materials in sensors, 12 catalysts, 13 drug delivery carrier, 14 gene delivery, 15 an adsorbent 16 , 17 and also as an antidote agent. 13 In this regard, Farjadian et al reported that EDTA modified MS could be potent antidote agents while assessed in vitro and in vivo in adsorption of iron 18 and copper.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another important peak of the MCM-41 framework was found at 800 cm −1 which showed the presence of Si–O stretching vibration. 31 Similarly, the ISM Zeolite showed all of the peaks that were identified in the FTIR analysis of M Zeolite, but an additional broad peak was found spanning from 3600 cm −1 to 3400 cm −1 which was due to stretching vibration of the N–H bond of TMSPTA. Another characteristic peak of C–N bond stretching was found at around 1300 cm −1 which further confirmed the presence of TMSPTA in ISM Zeolite.…”
Section: Resultsmentioning
confidence: 81%
“…The synthesis of mesoporous MCM-41 (ref. 31) was carried out by stirring CTAB (0.25 g) in 240 mL of DI water and 3.5 mL of 2 M NaOH solution at 80 °C for 30 min. Subsequently, 4.7 g of TEOS was added that initiated the precipitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation